Yiqi Fumai Lyophilized injection protects cardiac contractility in a rat model of heart failure with reduced ejection fraction by modulating SERCA2 - Yongwei Nie; Lu Chen; Yanxin Zhang; Yuqing Yao; Zizhuo Xue; Na Guo; Meixiu Wan; Zhi Li; Chunhua Liu; Dekun Li; Aichun Ju (Phytomedicine Plus)
Background: Yiqi Fumai Lyophilized Injection (YQFM) is a plant-derived preparation that shows protective effects against cardiac dysfunction in both human and animal models. In heart failure (HF), proteins involved in Ca2+ regulation, such as sarcoplasmic/endoplasmic reticulum Ca2+ transporting protein 2 (SERCA2) and cardiac ryanodine receptor 2 (RyR2), are dysfunctional. Compensation for the malfunction of these proteins is considered a practical option for restoring heart function. Methods: Coronary artery ligation was used to induce heart failure with reduced ejection fraction (HFrEF) in Sprague-Dawley rats. YQFM was administered via intravenous injection for two weeks. Cardiac contractility was evaluated using echocardiography. Hematoxylin and Eosin (H&E) staining, Masson's trichrome staining, western blotting, and immunohistochemical analysis were performed to evaluate myocardial damage and investigate the underlying molecular mechanisms. In vitro, H9C2 cells were subjected to oxygen and glucose deprivation. Western blotting and immunofluorescence staining were used to assess the expression of key Ca2+-handling proteins in the H9C2 cell models. Results: Twenty-five compounds, mainly ginsenosides, were identified in YQFM. In rats with HFrEF, treatment with YQFM or metoprolol prevents deterioration of cardiac contractility. YQFM caused a patchy delay in the downregulation of SERCA2 in the myocardium, resulting in reduced dilation of the left and right ventricles, thereby preventing left ventricular remodeling. In H9C2 cell models, our results demonstrated that YQFM partially prevented defects in SERCA2. Conclusion: Our study demonstrated that YQFM may function as a positive cardiac contractility modulator and therapeutic agent for cardiac protection by restoring SERCA2 expression in cardiomyocytes in HF after myocardial infarction (MI).